Suriname. Significant achievements 2021 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Suriname during 2021 are identified, with respect to the needs and interests of the country, strengthening in issues of apiculture, composting, agrotourism, livestock. fishing, climate-smart technology. Likewise, work was done on the cultivation of solanaceae, especially wild eggplant (Solanum stramonifolium). Finally, the market and opportunities for women's agricultural businesses were promoted, as well as guaranteeing access to drinking water, through the collection of rainwater.